KERANGKA KERJA AFILIASI KEMITRAAN ANTARA UNIVERSITAS, UMKM, DAN BANK LOKAL: MODEL PENGEMBANGAN INDUSTRI EKONOMI KREATIF - Catarina Wahyu Dyah Purbaningrum (FEB Universitas Sultan Ageng Tirtayasa, 2020)
The university has the responsibility of implementing Tri Dharma Perguruan Tinggi, one of which is community service. Higher education continues to look for opportunities to collaborate with other institutions. This collaboration can be with industry, the business sector, and the MSME (Small & Medium Enterprises) sector. Higher education can collaborate with local banks, umkm in developing creative industries. SMEs have a variety of creative business ideas, human resources and several other resources, but often have some weaknesses. These weaknesses can be in the form of financial weaknesses, and weaknesses in organizational management. Local banks can take a role in providing loan services to the micro sector and provide education about good financial management. Likewise, universities can take the role of sending the best people to provide education and organizational management assistance. The method of cooperation of the three parties is expected to provide benefits and strengthen the parties that cooperate with each other. Another expected benefit is the continued impact of good creative industry sector assistance in the form of regional economic revolving supported by the creative industry sector. This research provides information to the public about the framework of cooperation between universities, local banks and MSMEs.